Effect of AGG Interruptions on FMR1 Maternal Transmissions - Villate, Olatz; Ibarluzea, Nekane; Maortua, Hiart; de la Hoz, Ana Belén; Rodriguez-Revenga, Laia; Izquierdo-Álvarez, Silvia; Tejada, María Isabel (Frontiers in Molecular Biosciences, 2020)
There are four classes of CGG repeat alleles in the FMR1 gene: normal alleles have up to 44 repeats; patients with fragile X syndrome have more than 200 repeats; those between 55-200 CGGs are considered FMR1 premutation alleles, because they are associated with maternal expansions of the number of CGGs in the next generation and finally, alleles between 45-54 CGGs are called intermediate or gray zone alleles. In these last categories, the stability depends on the presence of AGG interruptions, which usually occurs between 9-10 CGGs. In this context, we have studied retrospectively 66 women with CGG repeats between 45 and 65, and their offspring. In total 87 transmissions were analyzed with triplet repeat primed PCR using AmplideX® FMR1 PCR (Asuragen, Austin, TX, USA) and we found that alleles with CGG repeats between 45 and 58 do not expand in the next generation except two cases with 56 repeats and 0 AGG interruptions. Furthermore, we have found four females with alleles with more than 59 CGG repeats and 2 AGG interruptions that do not expand either. Alleles from 56 CGG repeats without AGGs expand in all cases. In light of these results and those of the literature, we consider that the risk of unstable transmissions should be based on the presence or absence of AGG interruptions and not on the classical cutoffs which define each category of FMR1 alleles. The application of these results in the genetic and reproductive counseling is essential and AGG interruptions should always be studied.